Development of Safe Green Produce Grower Group of Smallholder Farmers in Phranakorn Si Ayutthaya, Bang Ban, and Bang Pahan Districts, Phra Nakhon Si Ayutthaya Province - Sirikesorn, Laongsri (Area Based Development Research Journal, 2021)
Safe green produce grower group of small farmers in Phranakorn Si Ayutthaya, Bang Ban, and Bang Pahan districts, Phranakorn Si Ayutthaya province encountered problems when selling green produce in general vegetable markets. Especially, there are issues when growers are unable to meet the market demands, and the green produce have no standard certification for green produce safety and cultivation process quality. This study aims to upgrade the smallholder farmers of safe green produce by adjusting the management and operation as the product will be guaranteed to reach the niche consumer groups in its high quality. The participatory research involves 27 participants from 3 grower community enterprises. This research process entails several aspects: 1) educating the farmer members about the good agricultural practice (GAP) scheme, 2) engaging farmers in group planning and operation, 3) implementing a mechanism for group members participation, 4) networking and expanding distribution channels for safe green produce 5) monitoring and evaluating the work process. The results show positive changes in the safe vegetable produces of the community enterprises. The redesign of group working style with clear production plans following the market demand, the allocation of cultivation areas for members, and the preparation for GAP scheme have firstly led to two members of safe green produce enterprises in Phranakorn Si Ayutthaya district being certified for GAP standards. Secondly, the higher price of safe vegetables in niche markets results in an increment of 15 percent average income. Thirdly, the safe green produce network with other districts has been established, and the members of community enterprise groups continue to operate the safe vegetable cultivation process to obtain certification in the future.